The effectivity of banana leaf-filtered cloth face masks as an alternative protection during the pandemic - Mohamad Saifudin Hakim; Mumtihana Muchlis; Fitra Duhita; Rita Dian Pratiwi (Intelektual Pustaka Media Utama, 2022)
The main transmission route of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is through individual droplets of respiratory secretions. Accordingly, the most basic preventive measure is wearing a face mask. Since the issue of medical waste during the pandemic is concerning, developing face masks made of reusable and biodegradable materials is necessary. This study aimed to develop